Higher Derivations Satisfying Certain Identities in Rings - Amal S. Alali; Shakir Ali; Naira N. Rafiquee; Vaishali Varshney (Journal of Mathematics)
Let n and m be fixed positive integers. In this paper, we establish some structural properties of prime rings equipped with higher derivations. Motivated by the works of Herstein and Bell-Daif, we characterize rings with higher derivations D=dii∈N satisfying (i) dnx,dmy∈ZR for all x,y∈R and (ii) dnx,y∈ZR for all x,y∈R.